Trichoblastoma and trichoblastic carcinoma in the head and neck region - Nutan Patel; Shadaab Mumtaz; Ravinder Pabla (Elsevier, 2021)
Trichoblastomas are benign cutaneous adnexal tumours which originate in the hair follicle germs. They are considered to be extremely rare and usually present in the head and neck region. Clinically, they present as flesh-coloured nodular growths mimicking the more commonly found basal cell carcinoma (Stanoszek et al., 2017 Nov) [1]. These tumours can potentially undergo malignant transformation which again is extremely infrequent.